A Selection Model of Hedonic House Values and Rents - Jonathan Halket; Lars Nesheim; Florian Oswald (European Regional Science Association (ERSA), 2015)
We use a large repeated cross-section of houses to estimate a selection model of the supply of owner-occupied and rental housing. We find that physical characteristics and unobserved heterogeneity and not location are important for selection. We interpret this as strong evidence in favor of contracting frictions in the rental market relating to maintenance and modification of a dwellings physical characteristics.
Keywords: 330